From French community to Missouri town Ste. Genevieve in the nineteenth century - Stepenoff, Bonnie, 1949-; ebrary, Inc. (Columbia : University of Missouri Press, 2006)
"Examines the historical circumstances, legal institutions, and popular customs of Ste. Genevieve, Missouri's oldest permanent settlement, to discuss how French and Spanish residents, German immigrants, and American settlers compromised on issues of education, religion, property laws, and women's rights to achieve order and community before and after the Louisiana Purchase"--Provided by publisher.
Ste. Genevieve in 1803 -- The old French aristocracy -- Americans in a French community -- German influx -- Becoming an American town -- Law and order in Ste. Genevieve -- French women in an American republic -- Slavery and freedom -- Work and family in Ste. Genevieve -- Home, church, and school -- Life, death, and remembrance -- Holidays and celebrations -- Ste. Genevieve in 1885.
Includes bibliographical references (p. 207-217) and index.
Electronic reproduction.
Keywords: Sainte Genevieve (Mo.) -- History -- 19th century; Sainte Genevieve (Mo.) -- Social conditions; Sainte Genevieve (Mo.) -- Ethnic relations -- History -- 19th century; Electronic books